An unusual presentation of a Unicystic ameloblastoma in a child: a case report and literature review. (16th February 2017) - Besi, E.; O'Connor, N.; Conn, B.; Handley, T.; Ulhaq, A.
Abstract: An ameloblastoma is a benign but locally aggressive epithelial odontogenic neoplasm. It represents 10% of all tumours of the jawbone. In 80% of cases it is localised to the mandibular molar region and ascending ramus area, and is frequently associated with an unerupted tooth. It presents most commonly in the 3rd and 4th decades of life. This article reports an unusual presentation and management of a unicystic ameloblastoma in a child orthodontic patient with a literature review.